The democratization of the revocation of mayors’ terms in Ecuador and Colombia: At the crossroads of local governance - Erazo, Luis Carlos (2019)
Is there a connection between the democratization of the revocation of mayors’ terms in office and the stability of local governance? In order to answer this question this research develops a neo-institutional analysis and presents a qualitative methodological strategy that comparatively addresses two countries, Ecuador and Colombia. The institutional design that adopts revocations of terms for mayors is analyzed through the reviewal of constitutional documents and regulations in each country. This analysis is complemented by descriptive statistics that allow for the evolution of this device, as an alternative to exerting democratic control, not electoral of the mixed institutional type, to be observed. As a hypothesis, this article proposes that as the institutional design becomes less restrictive to activate the revocation of a term for mayors, the probability that the democratic control will undermine the stability of the local government will increase. Inversely, an institutional design that is more restrictive will reduce these probabilities. The empirical evidence shows that the launching of the Ecuadorian institutional design since the constitutional reforms of 2008 caused a series of revocations of terms for mayors that is unprecedented in the democratic history of the country. Meanwhile, in Colombia, despite the age of this device, the same situation has not taken place. The analysis concludes that the institutional design of the revocation of terms for mayors has become a double-edged sword for the stability of local governments.